The Role of Cultural Festivals in the Sustainability of Micro and Small Enterprises - Alvia Intan Magroaini; Fahmi Poernamawatie; Azhari Atul Aini; Sri Hastuti (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Business continuity refers to a company's ability to sustain growth and development in a competitive market while ensuring long-term sustainability and profitability. Micro and Small Enterprises (MSMEs) play a crucial role in the Indonesian economy, contributing 97% to the workforce and 60.4% to economic activity. This study analyzes the influence of Human Resources (HR), materials, and capital on MSME business sustainability, with festivals as a moderating variable, in Serang Beach, Blitar. Despite their significance, MSMEs face challenges in maintaining business continuity. This quantitative study used primary data from 52 MSME actors, analyzed using SmartPLS. The results showed that materials and capital positively affected business sustainability, while HR had no significant impact. Festivals strengthened the relationship between materials and capital and business sustainability but did not moderate the effect of HR. These findings provide new insights into the role of cultural festivals in enhancing MSME sustainability and highlight the importance of effective resource management in achieving a sustainable competitive advantage.